Video-Based Socialization Group Activity Therapy for Blended Learning; the Validity of Learning Media - Rosyad, Yafi Sabila; Kora, Firmina Theresia (Budapest International Research and Critics University, 2022)
The digital era and during the COVID-19 period, practicum activities are very constrained because they do not have supporting learning media. To support an effective learning process, one of them can be done using blended learning. The purpose of this research is to create a video-based learning media as a mental nursing practicum guide related to socialization group activity therapy and find out the results of expert validity tests related to video-based learning. This research is a descriptive study to test the validity of video-based learning media through a procedural development model. The validity test was carried out on material and media experts using a product development assessment instrument in the form of learning video learning media. The components of format, content, and language were declared valid by nine material experts and were declared to be highly qualified with an average score of 3.3. Five components (simplicity, cohesiveness, balance, shape, and color) were declared valid and one component (emphasis) was declared quite valid by two media experts with an average score of 3.25 and highly qualified for use. Video-based socialization group activity therapy learning media is declared valid and very feasible to be used as blended learning.